The Concept of Halal Tourism and The Fulfillment of Muslim Tourist Needs in Halal Tourism - Syah Putra, M. Febtian; Tucunan, Karina Pradinie (Halal Center ITS, 2021)
The purpose of this study is to give an overview of the concept of halal tourism and the fulfillment of the needs of Muslim tourists in halal tourism. The purpose of the development of halal tourism is to provide greater convenience for Muslim tourists to still be able to carry out their worship while traveling, showing that the most basic needs that are prioritized to be fulfilled in halal tourism are closely related to the activities of worship. There are at least 6 basic needs that Muslims need in their daily lives including when doing tourist activities, namely the need to purify with water, facilities for worship, halal food, tourist activities that do not conflict with Islamic values, Ramadan services, and recreational facilities/services with privacy. But please note that Muslims have heterogeneity in religious practice and obedience, so that the needs of each individual in traveling basically varies depending on their respective religious practices and obedience, so many parties propose the preparation of guidelines/provisions of minimum standards of needs of Muslim tourists that must be fulfilled.